Conceptualising energy nationalism in the context of climate change: framework and review - Żuk, Piotr; Conversi, Daniele; Żuk, Paweł (Frontiers in Energy Research, 2024)
This article argues that the more energy policies are circumscribed within the borders of individual nation states, the more difficult it will be to implement the climate action on a global scale. The authors shed light on the relationship between nationalism and the simultaneous challenges of environmental protection, energy transition and climate change mitigation. Based on the review of various publications referring to nationalism in the context of energy policy and energy transition, the authors conceptualise this notion. Energy nationalism is defined here as any political decision, economic action and ideological justifications used to circumscribe energy policy within the nation state and subordinate it to “national interests,” “national security” and the “protection of national sovereignty.” Energy nationalism should be distinguished from both economic nationalism and resource nationalism, yet they are part of a continuum, in which economic considerations are upheld in the pursuit of strict national “interests” and, therefore, of the ruling elites in each nation state. The article explores the differences and mutual interconnections between the three. It finally explains why the notion of energy nationalism may better render the ongoing conflict between resource-focused elites and the international community–particularly in the context of the current climate emergency.